Argumentation in mathematics: mediation by means of digital interactive storytelling - Giovannina Albano; Umberto Dello Iacono; Maria Alessandra Mariotti (Firenze University Press, 2016)
This work is framed in a wider research aimed at outlining an online interactive platform model organizing mathematical learning activities based on a Vygotskian approach. This paper reports on a pilot study concerning a first implementation of a mathematical Learning Activity, as part of an interactive digital storytelling in mathematics, aiming at developing students' argumentative competences. We present the outcomes of the protocols' analysis and discuss them with respect two main points: the production of arguments for supporting of the solution to a question and the different functioning of the device according to the student's attitude with respect to the story and the team work.   L'argomentazione in matematica: la mediazione attraverso il digital interactive storytelling Questo lavoro è inserito in una ricerca più ampia volta a realizzare un modello di piattaforma interattiva online che implementi Learning Activity in matematica basate su un approccio vygotskiano. Questo articolo riporta uno studio pilota riguardante una prima implementazione di un task matematico, come parte di un digital storytelling interattivo in matematica, che mira a sviluppare competenze argomentative negli studenti. Presentiamo i risultati delle analisi dei protocolli e li discutiamo rispetto a due punti principali: sviluppo nella produzione di argomentazioni a supporto della risoluzione ad un quesito e diverso funzionamento del dispositivo a seconda dell'atteggiamento dello studente rispetto alla storia e al lavoro di gruppo.